2010
DOI: 10.1371/journal.pgen.1000808
|View full text |Cite
|
Sign up to set email alerts
|

The Systemic Imprint of Growth and Its Uses in Ecological (Meta)Genomics

Abstract: Microbial minimal generation times range from a few minutes to several weeks. They are evolutionarily determined by variables such as environment stability, nutrient availability, and community diversity. Selection for fast growth adaptively imprints genomes, resulting in gene amplification, adapted chromosomal organization, and biased codon usage. We found that these growth-related traits in 214 species of bacteria and archaea are highly correlated, suggesting they all result from growth optimization. While m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
464
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 317 publications
(502 citation statements)
references
References 97 publications
34
464
4
Order By: Relevance
“…We estimated MGTs for bacterial communities by calculating MGTs in available whole-bacterial genomes by using the method described in ref. 57 and mapping the 16S rRNA sequences we collected to these genomes.…”
Section: Methodsmentioning
confidence: 99%
“…We estimated MGTs for bacterial communities by calculating MGTs in available whole-bacterial genomes by using the method described in ref. 57 and mapping the 16S rRNA sequences we collected to these genomes.…”
Section: Methodsmentioning
confidence: 99%
“…Although genetic data can provide precise information on cellular processes or metabolic pathways, they are generally blind to other ecologically relevant phenotypic traits such as the tolerance to certain abiotic conditions or the specific growth rate (but see Vieira-Silva and Rocha, 2010). Unlike 'macrobial' ecologists, who can directly observe phenotypic characters of plants and animals, microbial ecologists usually face situations where most of the phenotypes of their study organisms are unknown.…”
mentioning
confidence: 99%
“…Interestingly, it was established that codon usage skew is specific to metagenome as a whole and is independent of the bacterial community enriched in the metagenome data [75]. This suggested that bacterial genera in the same metagenome can exhibit variable codon usage preferences but overall the metagenome is characterized by an accumulative codon bias which differs from the other metagenome samples markedly just like an observation for single microbial species/genome [76,77].…”
Section: Using Population Genomes To Analyze Differential Codon Usagementioning
confidence: 93%